Mechanistic role of environmental toxicants in inducing cellular ferroptosis and its associated diseases - Hong Chen; Bingchun Liu; Peixin Xu; Huizeng Wang; Xin Guo; Gang Liu; Jianlong Yuan (Ecotoxicology and Environmental Safety)
Due to exposure factors such as industrial exhaust, sewage discharge, pesticide runoff, automobile exhaust, and fuel combustion, environmental toxicants are widely present in daily life. Organisms are exposed to these environmental toxicants through contaminated air, food, and drinking water, and these environmental toxicants enter the human body and cause cytotoxicity and diseases through various pathways. As a new cell death mode that is different from cell necrosis, apoptosis, and autophagy, ferroptosis are mainly dysregulation of intracellular iron metabolism, lipid metabolism disorders, and the dysregulation of the antioxidant defense system, leading to lipid peroxidation and ultimately to the rupture of the cell membrane, damage, and cell death. Studies have shown that environmental toxicants induce a series of diseases, such as digestive diseases, urinary diseases, respiratory diseases, neurological disorders, and reproductive diseases, through the above mechanisms. We elaborate the mechanism of common environmental toxicants in inducing ferroptosis and the related systemic diseases mediated through the ferroptosis to provide the theoretical basis for preventing and treating environmental toxicant-related diseases. Nonetheless, our understanding of ferroptosis remains incomplete. For example, mechanisms and methods for the selective control of ferroptosis remain elusive, elucidating these mechanisms and strategies may be critical for leveraging knowledge of ferroptosis to treat related diseases.